2009
DOI: 10.1375/acri.42.3.354
|View full text |Cite
|
Sign up to set email alerts
|

Ethnic Identity and Criminal Offending in a New Zealand Birth Cohort

Abstract: T here has been a great deal of debate and speculation regarding the high levels of involvement of Māori New Zealanders in the criminal justice system. The present investigation examined the role of Māoricultural identity in predicting criminal offending in a New Zealand birth cohort studied from birth to the age of 21. There were statistically significant (p < .0001) bivariate associations between both sole Māori identification and Māori/other cultural identification, and both (a) official convictions for pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
22
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 20 publications
4
22
0
Order By: Relevance
“…In a New Zealand study, Marie, Fergusson, and Boden (2008) found that – after controlling for socioeconomic status, family functioning factors, and individual factors – men and women reporting Maori ethnicity were at higher risk of both IPV victimization and perpetration, as well as higher risk of injuries related to IPV than were non Maori participants. Risk of IPV did not vary with the degree of Maori identity.…”
Section: Resultsmentioning
confidence: 99%
“…In a New Zealand study, Marie, Fergusson, and Boden (2008) found that – after controlling for socioeconomic status, family functioning factors, and individual factors – men and women reporting Maori ethnicity were at higher risk of both IPV victimization and perpetration, as well as higher risk of injuries related to IPV than were non Maori participants. Risk of IPV did not vary with the degree of Maori identity.…”
Section: Resultsmentioning
confidence: 99%
“…The association of ethnicity with IPV has been examined in some non United States studies. In a New Zealand study, Marie, Fergusson, and Boden (2008) found that -after controlling for socioeconomic status, family functioning factors, and individual factors -men and women reporting Maori ethnicity were at higher risk of both IPV victimization and perpetration, as well as higher risk of injuries related to IPV than were non Maori participants. Risk of IPV did not vary with the degree of Maori identity.…”
Section: Contextual and Developmental Characteristics And Behaviors Omentioning
confidence: 98%
“…As an extension of being engaged within the group or community of the desired identity, a person must have knowledge about the community, and know and use the language of the community in order to take on that identity. An important part of cultural and ethnic identity is the knowledge of cultural customs, beliefs, and values and the knowledge and use of the language spoken (Marie, Fergusson, and Boden, 2009). There must be commitment to the identity.…”
Section: Identity and Stigmamentioning
confidence: 99%